MAKNA TUMPENG DALAM SESAJI JAWA PERSPEKTIF AGAMA HINDU - Margiyono, Toto; Wahyasa, Sugeng Sapta (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
The Indonesian nation is a religious nation. This is reflected in the activities and behaviors of society that embody religious values. As is commonly known, there are still people who practice fasting, asceticism, and abstaining from certain actions or foods. This is evidence that Indonesia is a nation of faith that acknowledges the existence of God. In performing these ceremonies, the Javanese people always offer Tumpeng as a ceremonial medium. There are various types of Tumpeng used by the Javanese, depending on the purpose and intent of the ceremony. This study aims to understand the meaning of Tumpeng from the perspective of Hinduism. The Javanese people regard Tumpeng as a miniature representation of a mountain. Meanwhile, in Hinduism, mountains are considered sacred places as they are associated with Acchallalingga. Tumpeng is a traditional offering of the Javanese community that is commonly found in various ceremonies, such as slametan, kenduri, village cleansing rituals, and thanksgiving events. In modern times, Tumpeng is not only used for sacred ceremonies but also for other celebrations, such as birthdays, thanksgiving events, business openings, and more. The conical-shaped rice is typically placed on a tampah, a circular woven bamboo tray, surrounded by various side dishes and vegetables. Tumpeng symbolizes a mountain, but in reality, not everyone understands that mountains hold symbolic significance in Javanese traditions. Upon closer examination, Tumpeng, lingga, and mountains share the same conceptual framework: Tumpeng is placed on a tampah, lingga rests on yoni, and mountains stand upon the ocean.